At the root of participatory approaches: uncovering the role of accompaniment. Issue 5 (4th July 2018) - Schnyder von Wartensee, Ilaria
ABSTRACT: This article examines the impact of a participatory development project in rural Uganda and offers explanations for the results obtained. Though successful in facilitating the creation of specific goods and services, the project did not fully realise its intended outcome: empowering local actors and generating lasting human development. These mixed results were the consequence of inconsistent dialogue and listening among the actors, often resulting in a lack of genuine accompaniment. In evaluating community engagement through the lens of accompaniment, the study considers the potential for participatory approaches to overcome often-asserted criticisms, namely the presence of dependency and elite capture.